Biosystematics and Morphological Variation of Selected Syzygium Species (Myrtaceae) from Ternate Island, Indonesia - Suparman; Fitria M Saleh; Zulkifli Ahmad; Marheny Lukitasari; Rusdi Hasan (UNIVERSITAS PGRI MADIUN, 2026)
The genus Syzygium (Myrtaceae) is one of the most diverse groups of tropical woody plants, characterized by high morphological variation and complex taxonomy. This study aimed to investigate the biosystematics, spatial distribution, and phenetic relationships of Syzygium species on Ternate Island, Indonesia, using morphological and multivariate approaches. Field exploration was conducted across five districts, and morphological data were collected from both vegetative and reproductive organs. A total of eight species were recorded, exhibiting heterogeneous distribution patterns ranging from widespread to localized occurrences. Multivariate analyses, including hierarchical cluster analysis and Principal Component Analysis (PCA), revealed consistent phenetic relationships, separating the species into two major groups. The first two principal components accounted for 78.62% of the total variation, with fruit-related characters—particularly fruit size and flesh thickness—identified as the main determinants of species grouping. A dichotomous key based on diagnostic morphological traits was developed to facilitate accurate species identification. These findings highlight the importance of reproductive characters, especially fruit morphology, in species delimitation within Syzygium. This study provides a valuable baseline for taxonomy, biodiversity assessment, and conservation, and underscores the continued relevance of morphology-based biosystematics in tropical plant research.